In situ generated PtNPs to enhance electrochemiluminescence of multifunctional nanoreactor COP T4VTP6 for AFB1 detection. (15th January 2023) - Lv, Xiaoyi; Tan, Fei; Miao, Tian; Cui, Bo; Zhang, Jianguo; Fang, Yishan; Shen, Yizhong
Highlights: An ECL immunosensor for AFB1 based on illuminant COP T4 VTP6 and quencher Fc-CHO/Phe. COP T4 VTP6 acted as a nanoreactor to catalyze and protect the formation of PtNPs. The in situ generated PtNPs served as coreaction accelerator. ECL response increased with increasing AFB1 via competition quenching mechanism. The proposed system provides a great application platform. Abstract: Herein, a competitive quenching electrochemiluminescence immunosensor towards aflatoxin B1 (AFB1 ) detection was constructed by in-situ forming platinum nanoparticles (PtNPs) on ECL emitter COP T4 VTP6 and effective ECL signal quencher Fc-CHO/Phe. In this system, cationic covalent organic polymer COP T4 VTP6 emitted stronger cathode ECL signal at 765 nm, it acted as an interesting nanoreactor to immobilize PtCl6 2− through electrostatic adsorption, and directly in situ catalyzed the redox reaction to produce PtNPs without adding any external reducing agent, where PtNPs not only served as the substrate for antibody immobilization, but also played the role of coreaction accelerator to catalyze the production of SO4 −, significantly improving more stable ECL signal. Moreover, the Fc-CHO/Phe labeled BSA-AFB1 was used for competitive reaction. Based on the efficient sensing strategy, ECL signal increased accordingly and exhibited linear signal responses with increasing AFB1, which realized a detection limit of 4.56 fg/mL, providing a promising potential on food analysis.